Differential Diagnosis and Medical Therapeutics-A Treatise on Clinical Medicine - Rao, P. S. R. K. P Siva Rama Krishna (Jaypee Brothers Medical Publishers, 2020)
The objective of this book is to introduce the Differential Diagnosis and Medical Therapeutics-A Treatise on Clinical Medicine. A symptom-oriented approach book containing 45 day-to-day problems (40 symptom chapters and 5 appendices along with 103 illustrations), enriched with assiduous knowledge, covering the whole gamut of medicine with an easy flow for easy uptake, followed by 40 algorithms encompassing the salient features of the detailed information, furnished in the text. Three additional topics of absorbing interest are included in this edition, i.e. abnormal involuntary movements, incontinence, and sleep disorders. This book is principally intended for medical students and house-officers to comprehend what is perceived by them in the wards, besides for those preparing for higher examinations.